The influence of financial sponsors on the post-IPO performance : Evidence from the Nordics - Tuovio, Antti; Iivonen, Oiva (My University, 2025)
This thesis investigates how financial sponsorship affects the performance of initial public offer ings (IPOs) in the Nordics. The analysis covers both short-term underpricing and long-term stock performance, examining whether sponsorship influences both outcomes. The research focuses on IPOs listed between 2013 and 2022 in Finland, Sweden, Norway, and Denmark. Sponsored IPOs are defined as offerings where a financial sponsor (PE or VC) held an ownership stake pre-listing. Short-term performance is measured through first-day returns (un derpricing), and long-term performance is measured using Buy-and-Hold Abnormal Returns (BHAR) over a 36-month post-IPO period. The final sample comprises 270 IPOs, of which 109 are classified as sponsored and 161 are non sponsored. The study employs a multivariate regression model for underpricing and BHAR both to evaluate differences in performance while controlling for firm-specific factors such as size, leverage, and market timing. Long-term returns are benchmarked against the MSCI Nordic Coun tries index, which includes listed companies only from the same countries as our IPO sample consists of. While existing literature has examined the effects of sponsor backing in IPOs, studies focused on the Nordic region remain scarce, and this thesis aims to fill that gap by providing empirical evidence with new data. The results of this study show no strong or consistent evidence that financial sponsorship affects IPO underpricing. While some models suggest marginal significance for reduced underpricing when controlling for size and leverage, the full model does not support this finding. In the long term analysis, sponsored IPOs do not appear to outperform non-sponsored ones, although some indications of worse performance emerged; these results were not consistent across all models. What this study found was that IPO’s conducted during hot market periods consistently had higher underpricing and underperformed over the 36-month post-listing period, likely due to initial overvaluation and investor sentiment at the time of the issuance.

Tämä pro gradu -tutkielma tarkastelee, kuinka taloudellinen sponsorointi vaikuttaa listautumis antiin (IPO) osallistuvien yritysten osaketuottoihin Pohjoismaissa. Analyysi kattaa sekä lyhyen aikavälin alihinnoittelun että pitkän aikavälin tuottokehityksen ja selvittää, vaikuttaako sponso rointi näihin kahteen asiaan. Tutkimus keskittyy vuosina 2013–2022 Suomessa, Ruotsissa, Norjassa ja Tanskassa toteutunei siin listautumisiin. Sponsoroiduiksi IPO:iksi määritellään ne listautumiset, joissa taloudellinen sponsori (pääomasijoittaja tai Venture Capital-sijoittaja) omisti osuuden yrityksestä ennen lis tautumista. Lyhyen aikavälin suorituskykyä mitataan ensimmäisen pörssipäivän tuotolla (alihin noittelu), kun taas pitkän aikavälin kehitystä arvioidaan Buy-and-Hold Abnormal Returns (BHAR) -menetelmällä 36 kuukauden ajanjaksolla listautumisen jälkeen. Tutkimusaineisto koostuu 270 listautumisesta, joista 109 on luokiteltu sponsoroiduiksi ja 161 ilman taloudellista sponsorointia toteutetuiksi. Eroja listautumisten tuottokehityksessä analy soidaan monimuuttujaregressiomalleilla sekä alihinnoittelun että BHAR-mittarin osalta. Mal leissa kontrolloidaan yrityskohtaisia tekijöitä, kuten yrityksen kokoa, velkaantuneisuutta ja markkina-ajoitusta. Pitkän aikavälin tuottoja verrataan MSCI Nordic Countries -indeksiin, joka koostuu samoista maista kuin tutkimuksen IPO-aineisto. Vaikka aiemmassa kirjallisuudessa on tarkasteltu sponsoroinnin vaikutuksia listautumisiin, Poh joismaita koskevaa empiiristä tutkimusta on saatavilla vain vähän. Tämän tutkielman tavoit teena on osaltaan paikata tätä aukkoa tarjoamalla uutta aineistoon perustuvaa näyttöä. Tutkimuksen tulosten perusteella taloudellinen sponsorointi ei näyttäisi vaikuttavan johdonmu kaisesti alihinnoitteluun. Vaikka joissakin malleissa havaittiin viitteitä vähäisemmästä alihinnoit telusta sponsoroinnin yhteydessä yrityksen koon ja velkaantuneisuuden huomioon ottamisen jälkeen, tämä havainto ei säilynyt täydessä regressiomallissa. Pitkän aikavälin tarkastelussa sponsoroidut listautumiset eivät tuottaneet paremmin kuin ei-sponsoroidut, mutta tulokset ei vät kuitenkaan olleet tilastollisesti merkittäviä eri mallien välillä. Tutkimuksen selkein ja johdon mukaisin havainto oli se, että kuumina markkinajaksoina toteutetut listautumiset olivat keski määrin voimakkaammin alihinnoiteltuja ja tuottivat heikommin 36 kuukauden seurantajakson aikana. Tämä viittaa mahdolliseen alkuperäiseen yliarvostukseen ja sijoittajasentimentin vaiku tuksiin listautumishetkellä.
Keywords: share issues; Nordic countries; security market; sponsorship; listing (stock market); private equity investors; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance